2022
DOI: 10.1136/annrheumdis-2021-220873
|View full text |Cite
|
Sign up to set email alerts
|

Blocking GM-CSF receptor α with mavrilimumab reduces infiltrating cells, pro-inflammatory markers and neoangiogenesis in ex vivo cultured arteries from patients with giant cell arteritis

Abstract: BackgroundEffective and safe therapies are needed for the treatment of patients with giant cell arteritis (GCA). Emerging as a key cytokine in inflammation, granulocyte-macrophage colony stimulating factor (GM-CSF) may play a role in promoting inflammation in GCA.ObjectivesTo investigate expression of GM-CSF and its receptor in arterial lesions from patients with GCA. To analyse activation of GM-CSF receptor-associated signalling pathways and expression of target genes. To evaluate the effects of blocking GM-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“…Interestingly, MAV decreased intimal thickness, T-cell infiltration, and neo-vessel formation in a human artery-SCID (severe combined immunodeficiency) chimera model [ 105 ]. In this line, Corbera-Bellalta et al have recently demonstrated that MAV reduces infiltrating cells, pro-inflammatory markers and neoangiogenesis in ex vivo cultured arteries from patients with GCA [ 106 ]. In fact, MAV reduced the expression of molecules relevant to T-cell activation (HLA-DR) and Th1 differentiation (IFN-γ), the pro-inflammatory cytokines IL-6, TNFα and IL-1β, as well as molecules related to vascular injury (MMP-9, lipid peroxidation products and inducible nitric oxide synthase).…”
Section: Treatment Of Giant Cell Arteritismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, MAV decreased intimal thickness, T-cell infiltration, and neo-vessel formation in a human artery-SCID (severe combined immunodeficiency) chimera model [ 105 ]. In this line, Corbera-Bellalta et al have recently demonstrated that MAV reduces infiltrating cells, pro-inflammatory markers and neoangiogenesis in ex vivo cultured arteries from patients with GCA [ 106 ]. In fact, MAV reduced the expression of molecules relevant to T-cell activation (HLA-DR) and Th1 differentiation (IFN-γ), the pro-inflammatory cytokines IL-6, TNFα and IL-1β, as well as molecules related to vascular injury (MMP-9, lipid peroxidation products and inducible nitric oxide synthase).…”
Section: Treatment Of Giant Cell Arteritismentioning
confidence: 99%
“…In fact, MAV reduced the expression of molecules relevant to T-cell activation (HLA-DR) and Th1 differentiation (IFN-γ), the pro-inflammatory cytokines IL-6, TNFα and IL-1β, as well as molecules related to vascular injury (MMP-9, lipid peroxidation products and inducible nitric oxide synthase). Furthermore, MAV reduced CD34+ cells and neoangiogenesis in GCA lesions [ 106 ].…”
Section: Treatment Of Giant Cell Arteritismentioning
confidence: 99%
“…Current medications for GCA (eg, glucocorticoids and tocilizumab) target primarily the CD4 + T h 17 immune response, possibly leaving residual CD4 + T h 1 pathway activity, which may explain why a sizeable proportion of patients flare with these treatments. In contrast, GM-CSF blockade with mavrilimumab may address the pathogenic mechanisms of GCA more comprehensively via its demonstrated suppressive effects on macrophages, CD4 + T h 17 cells, and CD4 + T h 1 cells, including downregulation of IFNγ expression 22 23. However, further mechanistic research linked to clinical outcomes is needed before firm conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a multifunctional cytokine that modulates the biology of dendritic cells, CD4 + T-cells and macrophages 18. Preclinical research has implicated GM-CSF in the pathogenesis of GCA 19–22. GM-CSF, its receptor, and downstream signalling molecules are expressed by immune and endothelial cells in temporal arteries from patients 19–22.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation